A review of how magnetic resonance imaging can aid in case management of common pathological conditions of the equine foot. (12th January 2016) - Barrett, M. F.; Frisbie, D. D.; King, M. R.; Werpy, N. M.; Kawcak, C. E.
Summary: Magnetic resonance imaging (MRI) has become a valuable tool for the diagnosis of a multitude of conditions previously grouped into the vague diagnosis of palmar heel pain based on the response to palmar digital nerve diagnostic analgesia. The use of MRI not only determines a specific pathological diagnosis of the numerous structures within the foot but also the findings of the MRI help direct treatment and rehabilitation protocols, as well as providing prognostic information. Common injuries include damage to the navicular apparatus, deep digital flexor tendon, arthropathy of the distal interphalangeal joint and desmopathy of the collateral ligaments of the distal interphalangeal joint. This article reviews common MRI abnormalities in the equine foot and how treatment can be directed by the findings. Medical and surgical treatment options, as well as shoeing and rehabilitation protocols, are also discussed in relation to MRI findings. Using MRI can help create a more individually tailored and case‐specific treatment regimen, which can, in turn, promote a more positive outcome in equine cases.